PENTINGNYA ANALISIS LINGKUNGAN INTERNAL BAGI PENCAPAIAN TUJUAN LEMBAGA PENDIDIKAN ISLAM - Weni Puspita (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2016)
The problems that occurred in Islamic educational institutions is the low achievement of the goals obtained as a result of negligence analyze the internal factors at the beginning of the event, so the design process is organized and the activities carried out are not optimal. This study uses the science of strategic management approach. The conclusion of this research is the analysis of internal factors for Islamic educational institutions important to know the advantages and disadvantages of the institution in order to prepare a work plan and the right activities and anticipate the worst happens in the coming work processes so that results can be achieved also expected. Excess agencies may be selling to work and improve competitiveness. Disadvantages are known at the beginning to be a record for the agency to look for solutions, anticipation, and other alternatives to cover and to empower them to keep potential.